International frictions and optimal monetary policy cooperation: analytical solutions - Matthieu Darracq Pariès (European Central Bank (ECB), 2007)
This paper analyzes the implications of price-setting and incomplete financial markets for optimal monetary cooperation. The main objective is to provide the basic intuitions concerning the role of the main international frictions on optimal policy within a simple Dynamic Stochastic General Equilibrium model. We concentrate on a symmetric two-country DSGE with home bias, incomplete financial markets internationally and imperfect competition together with nominal price rigidities in which the export prices can be denominated either in the producer currency (PCP) or in the consumer currency (LCP). In addition, the model can account both for efficient and inefficient shocks. Our main results are derived in polar cases with efficient steady state and for which the design of the optimal policy is specifically illustrative and can be expressed in terms of targeting rules. In particular, the paper gives some new insights on the optimal exchange rate regime given the structure of shocks and the exchange rate pass-through, as well as on the optimal stabilization of CPI and PPI inflation. We also put into perspective the implication of financial autarky on the optimal management of international spillovers.
Keywords: E5; F4; 330; DSGE Models; New open economy macroeconomics; optimal monetary policy; Dynamisches Gleichgewicht; Neue Makroökonomik offener Volkswirtschaften; Optimaler Währungsraum; Geldpolitik; Geldpolitisches Ziel; Theorie